Quality Seed Production of Soybean in India: Current Status and Challenges - MENIARI TAKU; MANISHA SAINI; AKSHAY TALUKDAR (Seed Research, 2025)
Soybean, the primary oilseed crop in India, has experienced significant growth in recent years, yet its productivity remains relatively low at around 1 ton per hectare. One major factor contributing to this underperformance is the inadequate supply of quality seeds. Despite increasing demand for breeder seeds, production and availability have not kept pace, negatively impacting soybean yields. To address these challenges, strategic planning and policy support are essential. Expanding the seed production network, enhancing infrastructure, implementing scientific storage and handling practices, and providing training on seed production and supply chain management are crucial steps towards improving quality seed production and availability. Additionally, the seed replacement rate for soybean needs urgent attention. Collaboration between private players, farmers’ producer groups, and government agencies can bolster seed production and ensure timely availability of quality seeds. Scientific production practices, including grading, packaging, and storing, are also critical aspects to consider. By implementing these measures, India can significantly enhance the production and availability of soybean seeds, driving increased yields and supporting the growth of the oilseed sector.